2020
DOI: 10.1038/s41598-020-75006-8
|View full text |Cite
|
Sign up to set email alerts
|

Diminished corticomotor excitability in Gulf War Illness related chronic pain symptoms; evidence from TMS study

Abstract: Chronic diffuse body pain is unequivocally highly prevalent in Veterans who served in the 1990–91 Persian Gulf War and diagnosed with Gulf War Illness (GWI). Diminished motor cortical excitability, as a measurement of increased resting motor threshold (RMT) with transcranial magnetic stimulation (TMS), is known to be associated with chronic pain conditions. This study compared RMT in Veterans with GWI related diffuse body pain including headache, muscle and joint pain with their military counterparts without G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…We found that high ICF correlates with high pain intensity but not SICI. SICI and ICF have been recognized as markers of the reorganization of sensorimotor pathways in chronic pain states; however, their roles seem to be associated with distinct facets of chronic pain since both markers are not always correlated [ 45 , 46 , 47 ]. Previous evidence has suggested that ICF is modified by GABA-meditated inhibition that could be independent of SICI changes (predominant GABA-A networks).…”
Section: Discussionmentioning
confidence: 99%
“…We found that high ICF correlates with high pain intensity but not SICI. SICI and ICF have been recognized as markers of the reorganization of sensorimotor pathways in chronic pain states; however, their roles seem to be associated with distinct facets of chronic pain since both markers are not always correlated [ 45 , 46 , 47 ]. Previous evidence has suggested that ICF is modified by GABA-meditated inhibition that could be independent of SICI changes (predominant GABA-A networks).…”
Section: Discussionmentioning
confidence: 99%
“…Previously deployed GWV who meet the diagnostic criteria of GWI and study inclusion criteria of GWI-HAP for two interventional trials for pain and headache were identi ed. All Veterans included in the current comparison were required to the meet the inclusion criteria of male or female Veterans in the age range of 18 to 65 years old who served in the Persian Gulf for at least 30 consecutive days between August 1990 and July 1991 30 , both Center for Disease Control and Prevention (CDC) 31 and Kansas 32 Criteria for GWI, and International Headache Society Criteria for Migraine Headaches Without Aura 33 (see Table 3).…”
Section: Methodsmentioning
confidence: 99%
“…For daily muscle and joint pain, an average pain score greater than or equal to 3/10 on a NRS was required. 30 Veterans were excluded from the study if they had: history of pacemaker implant; any ferromagnetic material in the brain or body that would prevent them from completing an MRI scan; history of dementia; major psychiatric diseases such as bipolar disorder or schizophrenia; or life-threatening diseases; presence of any chronic neuropathic pain; history of seizures; pending litigation; low back pain with mechanical origins; lack of ability to understand or speak English; history of traumatic brain injury; chronic tension or cluster headaches.…”
Section: Methodsmentioning
confidence: 99%
“…This amplified MEP response in chronic pain has been interpreted as a cortical reorganization due to an imbalance between the inhibitory and excitatory systems (110)(111)(112). Interestingly, although, the MT increased in some cases (113,114), it tended to remain unchanged in both acute (115) and chronic pain (65,116) in most studies.…”
Section: Tms Measurements In Painmentioning
confidence: 98%